THE IMPORTANCE OF BUDDHIST EDUCATION AND HUMAN RESOURCE DEVELOPMENT AT PREY SPEU PRIMARY SCHOOL, CAMBODIA - Dr. By Loeung; Nhe Nara (SUJANA: Education and Learning Review, 2025)
This study examined the role of Buddhist education in human resource development at Prey Speu Buddhist Primary School in Phnom Penh, Cambodia. Employing a mixed-methods design, the research investigated how Buddhist education contributes to cognitive, affective, and behavioral development among students. Data were collected through structured questionnaires administered to 70 participants, including teachers and students from grades 5 and 6, supplemented by in-depth interviews with five key informants comprising senior teachers and school administrators. The survey instrument demonstrated strong internal consistency, with missing data handled through listwise deletion. Quantitative findings revealed strong participant recognition of Buddhist education's importance across multiple dimensions, with 77.14% strongly agreeing it teaches citizenship and appropriate behavior, 74.28% valuing the integration of religious and universal knowledge, and 71.42% recognizing its role in developing critical thinking. Regarding specific contributions to human resource development, 88.57% of participants acknowledged the school provides educational opportunities for orphans, 82.85% recognized access for poor students, and 75.71% agreed the curriculum provides sufficient knowledge for higher education progression. Qualitative interviews identified three major themes: holistic student development through integrated practice, educational accessibility as social mission, and balancing secular curriculum with Buddhist teachings. The integration of quantitative and qualitative evidence demonstrates that Buddhist education contributes substantially to human resource development through ethical formation, contemplative practices, comprehensive support systems, and integrated curriculum combining ministry requirements with Buddhist principles, thereby preparing students for both practical livelihood and moral development.